Contact dermatitis-like cutaneous leishmaniasis in a Libyan HIV patient - Al-Dwibe, Hamida (BioMed Central, 2014)
BACKGROUND: Cutaneous leishmaniasis (CL) is one of the common tropical protozoal diseases caused by various Leishmania species, and transmitted by the sand-fly vectors, Phlebotomus and Lutzomyia species. Herein, we report for the first time a case of CL that presented as large eczematous plaques occurring on the dorsi of both feet in a Libyan drug addicted, alcoholic patient with HIV infection. FINDINGS: A 34 year-old HIV-positive, alcoholic, drug addicted Libyan male presented to us with a history of a non-itchy skin lesions on the dorsi of both feet of 5-weeks duration. Systemic and topical antibiotics were given without improvement. Diagnosis of this patient was confirmed by observation of Leishmania amastigote bodies in stained slit-skin smear skin biopsy. After parenteral administration of sodium stiboglyconate (Pentostam) (20 mg/kg/day) for 28 days the lesions did not show any marked improvement. Concurrently, combination therapy of oral rifampicin (600 mg/day) and isoniazide (300 mg/day) was given for 8 weeks. Complete healing of lesions was achieved after this treatment and skin-slit smears turned negative. CONCLUSIONS: Localized cutaneous leishmaniasis should be remembered in deferential diagnosis of unresponsive contact dermatitis especially for HIV-positive patients in CL endemic areas. This patient was not responding to Pentostam therapy, which is not very common in Libya. Interestingly, combination of oral rifampicin (600 mg/day) and isoniazide (300 mg/day) can be a successful alternative therapy.